Transmission of hepatitis C virus in HIV‐positive and PrEP‐using MSM in England. Issue 7 (12th March 2020) - Bradshaw, Daniel; Vasylyeva, Tetyana I.; Davis, Chris; Pybus, Oliver G.; Thézé, Julien; Thomson, Emma C.; Martinello, Marianne; Matthews, Gail V.; Burholt, Ruth; Gilleece, Yvonne; Cooke, Graham S.; Page, Emma E.; et al.
Abstract: We sought to characterize risk factors and patterns of HCV transmission amongst men who have sex with men (MSM). MSM with recently acquired HCV (AHCV) were prospectively recruited ('clinic cohort') between January and September 2017. Clinical data and risk behaviours were identified and blood obtained for HCV whole genome sequencing. Phylogenetic analyses were performed, using sequences from this cohort and two other AHCV cohorts, to identify transmission clusters. Sixteen (40.0%) men in the clinic cohort were HIV‐negative MSM. HIV‐negative MSM were younger than HIV‐positive MSM; most (81.3%) had taken HIV PrEP in the preceding year. Eighteen men (45.0%) reported injection drug use; most (34, 85.0%) reported noninjection drug use in the last year. Most in both groups reported condomless anal sex, fisting and sex in a group environment. Few (7, 17.5%) men thought partners may have had HCV. There were 52 sequences in the HCV genotype 1a phylogeny, 18 from the clinic cohort and 34 from other AHCV cohorts; 47 (90.4%) clustered with ≥1 other sequence. There were 7 clusters of 2‐27 sequences; 6 clusters contained HIV‐negative and HIV‐positive MSM and 1 cluster only HIV‐positive MSM. Four of these clusters were part of larger clusters first described in 2007. PrEP‐using MSM are at risk of HCV, sharing similar risk factors to HIV‐positive MSM. Phylogenetics highlights that PrEP‐using and HIV‐positive MSM are involved in the same HCV transmission networks. Few men demonstrated HCV awareness and risk reduction strategies should be expanded.